7(3x-2)=6(x-2)-6

Simple and best practice solution for 7(3x-2)=6(x-2)-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(3x-2)=6(x-2)-6 equation:


Simplifying
7(3x + -2) = 6(x + -2) + -6

Reorder the terms:
7(-2 + 3x) = 6(x + -2) + -6
(-2 * 7 + 3x * 7) = 6(x + -2) + -6
(-14 + 21x) = 6(x + -2) + -6

Reorder the terms:
-14 + 21x = 6(-2 + x) + -6
-14 + 21x = (-2 * 6 + x * 6) + -6
-14 + 21x = (-12 + 6x) + -6

Reorder the terms:
-14 + 21x = -12 + -6 + 6x

Combine like terms: -12 + -6 = -18
-14 + 21x = -18 + 6x

Solving
-14 + 21x = -18 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-14 + 21x + -6x = -18 + 6x + -6x

Combine like terms: 21x + -6x = 15x
-14 + 15x = -18 + 6x + -6x

Combine like terms: 6x + -6x = 0
-14 + 15x = -18 + 0
-14 + 15x = -18

Add '14' to each side of the equation.
-14 + 14 + 15x = -18 + 14

Combine like terms: -14 + 14 = 0
0 + 15x = -18 + 14
15x = -18 + 14

Combine like terms: -18 + 14 = -4
15x = -4

Divide each side by '15'.
x = -0.2666666667

Simplifying
x = -0.2666666667

See similar equations:

| -9(n+7)-4=-85 | | 4x+21/32=7/8-1/16x-1/4 | | 2/5x-4=8-3/5x | | x^2-7/3x-2/3=0 | | -8(4b-4)+(33b-7)=0 | | -4.64+9.9t=10.3t | | 3(2x+1)=(2x+1)+(2x+1)+(2x+1) | | 3x-11+1/x-8 | | 11=y+13 | | 0.9(9x+6)=2.5-(x-3) | | -3n-1/2(-4-4n)=7 | | 283=3.14(5)l+(3.14)25 | | 5+(-3w+-12)=w+-7 | | -12.2y-8.68=-11.34-13.6y | | 2e^6= | | 3(3x-2)=7(x+6)+7 | | 1/2x-5=3x-10 | | 9x+6y=150 | | 283=3.14(5)l+25 | | 2(5x-3)-1=13 | | 6v+6=4v+2(v+3) | | 3.1-0.2a=1.5 | | m+m+5+m+8=84 | | 5-2p=7 | | -7.26+18p=6p-2.22+12.3p | | 3x+4y=75 | | 4x-48=36 | | 25.50x=12.50 | | -1=c-6 | | 6x+(3x-2)=14 | | -7v-5=-5v-9 | | x^2-7/3x-2/3 |

Equations solver categories